Impact of CHRO/CPO led best practices through HR department on SME Business Growth in India: A Literature Review - Das, Debashish; Nandal, Naveen (International Journal of Psychosocial Rehabilitation, 2020)
In the new normal, it is well established that the greatest asset for business is people. Organizations may have plants and machinery, ideas, finance, and technology, but human capital makes the difference. Whereas large organizations have understood the criticality of this aspect, small and medium enterprises (SME) are still warming up to the idea. Some SME have an HR department and use it effectively to implement people practices and run the organization professionally, whereas others make it a simple transactional and administration-focused function only to implement directions provided. In the process, the strength and rigor of better people practices that the HR department can deliver is compromised. This study aims to identify the impact that a CHRO/CPO and the HR department can make in SME organizations to grow the business professionally.